2019
DOI: 10.1371/journal.pone.0211194
|View full text |Cite
|
Sign up to set email alerts
|

3500 years of shellfish mariculture on the Northwest Coast of North America

Abstract: Ancient systems of mariculture were foundations of social-ecological systems of many coastal Indigenous Peoples. However, since such systems either do not leave tangible remains in the archaeological record, and/or are hard to date, we know little about their development and use. Clam gardens, traditional mariculture features located within the intertidal zone along the Northwest Coast of North America, are composed of a rock wall positioned at the low tide mark and a flattened terrace on the landward side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…After ∼3.5 ka, human–clam relationships in our study area intensify as indicated by the building of some of the first clam gardens (24). At this time, large settlements increase in number in Kanish and Waiatt Bays, filling all inhabitable coastal landforms and reflecting an increase in local human populations.…”
Section: Discussion: the Historical Ecology Of Human–clam Relationshipsmentioning
confidence: 98%
See 2 more Smart Citations
“…After ∼3.5 ka, human–clam relationships in our study area intensify as indicated by the building of some of the first clam gardens (24). At this time, large settlements increase in number in Kanish and Waiatt Bays, filling all inhabitable coastal landforms and reflecting an increase in local human populations.…”
Section: Discussion: the Historical Ecology Of Human–clam Relationshipsmentioning
confidence: 98%
“…Many large villages established at that time continued to be occupied until the late 1700s CE, at which time European diseases severely decreased Indigenous populations (25). Clam gardens were first constructed at some time around 3.5 ka, and they continued to be built and maintained, although in a much reduced way, into the mid-1900s (24). The number and extent of shell midden sites and the density of clam garden features (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiquity of this technology is truly prehistoric, meaning that there is no written tradition relating to it, but there is an aural tradition which is conserved by present day First Nations peoples, some of which can be found in the YouTube videos listed in Table 4. This coastal engineering activity, called clam gardens by western science, has played a significant role for many millennia in First Nations communities of the Pacific Northwest; certainly, for up to 11,500 years (Smith et al, 2019;Toniello et al, 2019). However, most of the gardens have not been tended for many decades and are in need of restoration.…”
Section: Ancient Clam Gardeningmentioning
confidence: 99%
“…These intertidal rock walls and associated terraces represent one of several coastal habitat alterations created over millennia by Coast Salish people to steward marine resources, increase clam productivity and ensure stable shellfish abundances adjacent to coastal communities to support economies, cultural practices and governance (Lepofsky et al 2015, Hul'q'umi'num -GINPR 2016. Recent radiocarbon dates and scientific investigations into taphonomic processes, indicate clam garden construction throughout Northern Quadra Island, British Columbia, began at least 3500 yr before present (Smith et al 2019). In addition to supplying a reliable food source for communities, clam gardening is integral to governance systems that dictated land use and stewardship, which continues to the present day (Deur et al 2015, Lepofsky et al 2015, Hul'q'umi'num -GINPR 2016.…”
Section: Coastal Humansmentioning
confidence: 99%